2008
DOI: 10.1088/0031-9155/53/22/018
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic characterization of soft tissue from dynamic finite element models

Abstract: An iterative solution to the inverse problem of elasticity and viscosity is proposed in this paper. A new dynamic finite element model that is consistent with known rheological models has been derived to account for the viscoelastic changes in soft tissue. The model assumes known lumped masses at the nodes, and comprises two vectors of elasticity and viscosity parameters that depend on the material elasticity and viscosity distribution, respectively. Using this deformation model and the observed dynamic data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Eskandari et al solved the time‐harmonic equations in a similar fashion using Levenburg–Marquardt. This implementation was later used in a study on bandpass sampling and was extended to employ mesh adaptation .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eskandari et al solved the time‐harmonic equations in a similar fashion using Levenburg–Marquardt. This implementation was later used in a study on bandpass sampling and was extended to employ mesh adaptation .…”
Section: Methodsmentioning
confidence: 99%
“…In Fovargue et al, computation times of approximately 50–90 seconds were reported for data sets with approximately 24 000–33 000 voxels for a mixed heterogeneous implementation with Tikhonov regularization (MATLAB with an Intel Xeon 4‐core, 8‐thread, 3.6 GHz processor). In Eskandari et al, compute times for the 2D heterogeneous direct method were compared with those of an iterative method and local method for varying image sizes (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…G. Jonsson small and the strain rates were rapid (faster than 0.5/s) [7], [16], [17]. modeling the frequency dependence of the elastic modulus in soft tissue is a key to gaining information about the existence of lesions.…”
Section: Introductionmentioning
confidence: 99%
“…However, estimation of both axial and lateral components of the motion is required for several elastography techniques [32], and has been shown to improve the reconstruction of elasticity images [3].…”
Section: Introductionmentioning
confidence: 99%